Features and Advantages of Supercritical CO2 Extraction of Sea Cucumber Cucumaria frondosa japonica Semper, 1868 - Alexander Zakharenko; Denis Romanchenko; Pham Duc Thinh; Konstantin Pikula; Cao Thi Thuy Hang; Wenpeng Yuan; Xuekui Xia; Vladimir Chaika; Valery Chernyshev; Svetlana Zakharenko; Mayya Razgonova; Gyuhwa Chung; et al. (Molecules, 2020)
Extraction process of Cucumaria frondosa japonica Semper, 1868, which are subspecies of Cucumaria frondosa (Gunnerus, 1767), were studied. It was shown that supercritical carbon dioxide extraction of holothuria was more effective than conventional solvent extraction. Step-by-step extraction with carbon dioxide followed by supercritical extraction with the addition of a co-solvent of ethanol can almost double the yields of extracts of triterpene glycosides, styrenes and carotenoids. Moreover, the fraction of triterpene glycosides practically does not contain colored impurities, in contrast to traditional ethanol extraction. The obtained extracts by HPLC in combination with tandem mass spectrometry (HPLC-MS/MS) identified 15 triterpene glycosides, 18 styrene compounds and 14 carotenoids. Supercritical extraction made it possible to obtain extracts with yields superior to conventional hexane and alcohol extracts. Moreover, such an approach with the use of supercritical fluid extraction (SFE) and subsequent profiling of metabolites can help with the study of holothuria species that are not as well studied.